Handbook for sugarcane cultivators - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Sugar cane by R Fauconnier 1993 140pp ISBN 0 333 57075 8 Pbk